Amalan penggunaan bahan bantu mengajar dalam kalangan guru cemerlang Pendidikan Islam sekolah menengah di Malaysia - Jasmi, Kamarul Azmi (Fakulti Pendidikan, Universiti Kebangsaan Malaysia, 2011)
This article aims to discuss the practice of using teaching aids (TA) Excellent Islamic Education Teachers (EIET) through a case study. This study was conducted in eight secondary schools in Malaysia using interview with the EIET, their colleagues, students, and also school principals senior assistants. The data were organized using the N'Vivo version 7.0 to develop theme and matrix table associated with the use of fuel EIET practices in schools. The findings show that there are 16 types of fuel used by the teaching and learning (T&L) EIET them and classified the patterns of fuel and not a pattern. There are six types of fuel that make use of practice patterns among the major EIET such as textbooks, and computer and LCD. The fuel side to form a pattern that is the circulation of paper and modules, mahjong paper, reference books, and pictures. While fuel is a chart pattern is forming, newspaper and cuttings, movie and video, reference work, OHP and transparencies, black and white boards, maujud materials, radio, tapes, and audio files, folios, and manila paper cards.